Inclusive Value Chains to Accelerate Poverty Reduction in Africa - Swinnen, Johan; Kuijpers, Rob (World Bank, Washington, DC, 2020)
The rapid transformation of agri-food value chains in Africa and other developing countries hasimportant implications for economic growth and poverty reduction. Policy makers increasinglyrecognize this but there is a need for a better understanding of what value chain transformationentails and what the main policy options are. This paper provides an overview and analysis ofdifferent value chain models that have emerged in the past decades and reviews the literatureon the main development implications. We discuss and categorize existing policy initiativesthat aim to stimulate inclusive value chain development. Based on this review we identifylessons and implications for policy makers.